PERSENTASE BAHAN PEMBUATAN KOMPOS (DAUN LAMTORO : SABUT BUAH LONTAR : PUPUK KANDANG SAPI) UNTUK MENGHASILKAN KOMPOS YANG BERKUALITAS - Aloysius Ng. Lende; Mochammad Hasan; Leny M. Mooy; Suryawati Suryawati (Partner, 2017)
Compost is organic material (organic waste) that has undergone a weathering process because of the interaction between microorganisms (bacteria decomposition) that work in it.  Organic materials such as leaves, grass, straw, the remains of twigs, branches and animal waste. In the open nature of compost can occur by itself through a natural process. But   the process lasts for so many years. Therefore the process needs to be accelerated with the help of human. The purpose of this study was to assess the percentage of good natural ingredients for the manufacture of quality compost. The experiment was conducted with single randomized block design (RBD) of compost (lamtoro: lontar fruit fiber: cow manure) with 6 percentage treatment and 4 repeat so that obtained 24 unit of experiment, that is: P1: leaf lamtoro 20% + 30% lontar fruit fiber + 50% cow manure, P2: 30%  leaf lamtoro + 20%  lontar fruit fiber +   50% cow manure, P3: leaf lamtoro 50% + 30%  lontar fruit fiber + 20%  cow manure, P4: 20%  leaf  lamtoro + 50%  lontar fruit fiber + 30%  cow manure,  P5: 30%  leaf  lamtoro  + 50%  cow   manure 20%,  P6 : leaf lamtoro 50% + 20%  lontar fruit fiber + 30% cow manure. Percentage of compost material from leaf lamtoro: lontar fruit fiber: cow manure on treatment P6 shows higher temperature and humidity than other treatments. Results of macro and micro nutrient analysis showed nutrients level from medium to high. The results of the C/N ratio analysis show low result when compared to the C/N ratio level status. Keywords: compost, leaf lamtoro, lontar fruit fiber, cow manure and percentage